Friend, Foe, or Food: What Influences Students' Attitudes Toward Animals?. (4th March 2021) - Morrison, Rachel; Maust-Mohl, Maria; Charlton, Kelly
ABSTRACT: Animals play a large role in society, yet attitudes about animals vary widely depending on individual differences in age, gender, experience with animals, and culture. The purpose of this study was to examine which factors, particularly geographic location, may influence college students' overall attitudes toward animal use. College students ( n = 297), age ranged from 18–54 years ( M = 19.88, SD = 2.89), from urban and rural schools in the US completed a survey that included demographics questions, the Animal Attitudes Scale (AAS), and the Belief in Animal Mind (BAM) scale. We predicted differences between urban and rural students' scores on the AAS and BAM scales and anticipated other factors, such as prior experience with animals, would positively influence students' responses. We also predicted that pro-animal welfare attitudes would be associated with the BAM. Scores on the AAS ( M = 3.41, SD = 0.59) and BAM ( M = 5.08, SD = 1.01) scales were positively related and suggested support for animal welfare and thinking. Our findings revealed that currently living in and growing up in rural areas significantly lowered AAS scores, while growing up in rural areas lowered BAM scores. Exploration of several demographic variables showed female students and those reporting experience with pets and service animals had higher AAS scores; BAM scores were higher for females and students with only service animal experience. However, experience with animals for hunting resulted in lower AAS scores. In addition, students using newspapers/magazines to learn about animals had higher AAS scores, and those visiting natural history museums had higher BAM scores. These results suggest several underlying cultural factors that shape college students' attitudes and beliefs about animals and the human–animal connection. Future studies should continue to investigate the influence of these and other factors on attitudes toward animal use and perceptions of animal thinking.